2022
DOI: 10.3389/fphys.2022.1041940
|View full text |Cite
|
Sign up to set email alerts
|

ER stress and calcium-dependent arrhythmias

Abstract: The sarcoplasmic reticulum (SR) plays the key role in cardiac function as the major source of Ca2+ that activates cardiomyocyte contractile machinery. Disturbances in finely-tuned SR Ca2+ release by SR Ca2+ channel ryanodine receptor (RyR2) and SR Ca2+ reuptake by SR Ca2+-ATPase (SERCa2a) not only impair contraction, but also contribute to cardiac arrhythmia trigger and reentry. Besides being the main Ca2+ storage organelle, SR in cardiomyocytes performs all the functions of endoplasmic reticulum (ER) in other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 134 publications
0
7
0
Order By: Relevance
“…Second, HEK 293 cells may not reflect ion channels and Ca 2+ handling proteins such as cardiac cells. Ca 2+ mishandling is a prominent feature in heart failure for laminopathies and intracellular Ca 2+ dysregulation is a central component for both atrial fibrillation, ventricular tachycardia, and ventricular fibrillation. ,, Thus, the identification of upstream modulators of key Ca 2+ handling proteins remains an important target for cardiac laminopathy disease modulation. We are actively working on resolving this with additional studies in iPSC-cardiomyocyte models.…”
Section: Discussionmentioning
confidence: 99%
“…Second, HEK 293 cells may not reflect ion channels and Ca 2+ handling proteins such as cardiac cells. Ca 2+ mishandling is a prominent feature in heart failure for laminopathies and intracellular Ca 2+ dysregulation is a central component for both atrial fibrillation, ventricular tachycardia, and ventricular fibrillation. ,, Thus, the identification of upstream modulators of key Ca 2+ handling proteins remains an important target for cardiac laminopathy disease modulation. We are actively working on resolving this with additional studies in iPSC-cardiomyocyte models.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged severe or persistent endoplasmic reticulum stress and protein misfolding can induce inflammatory responses and apoptosis, and promote myocardial remodeling ( Oakes and Papa, 2015 ; Narezkina et al, 2021 ; Ren et al, 2021 ; Ren et al, 2022 ). Endoplasmic reticulum stress (ERS) plays a key role in a variety of cardiovascular diseases, including fatal arrhythmias ( Sirish et al, 2021 ; Hamilton and Terentyev, 2022 ). Recent studies have documented that ERS plays a crucial role in the pathophysiologic basis of AF ( Sirish et al, 2021 ).…”
Section: Molecular Mechanisms Of Chemotherapy-related Cardiotoxicitymentioning
confidence: 99%
“…It has been shown that the ERS pathway regulates a variety of myocardial functions such as inflammatory response, apoptosis, and autophagy. Chronic ERS interferes with the redox state in the endoplasmic reticulum and reduces the expression of myocardial ion channel proteins, which leads to arrhythmogenesis ( Hamilton and Terentyev, 2022 ). The importance of ER and its signaling pathway in Dox-induced cardiotoxicity concerning inflammation, apoptosis, and autophagy suggests that it may be a key factor in the cardiotoxic effects of Dox-induced cardiovascular toxicity ( Minamino et al, 2010 ; Abdel-Daim et al, 2017 ; Akolkar et al, 2017 ; Wang et al, 2018 ; Yarmohammadi et al, 2021 ).…”
Section: Molecular Mechanisms Of Chemotherapy-related Cardiotoxicitymentioning
confidence: 99%
“…Cardiac calcium regulation is closely linked to cardiac contraction. The sarcoplasmic reticulum is the main source of calcium for myocardial contraction [48]. Calcium regulatory proteins such as the sodium-calcium exchanger (NCX), Ca 2+ -ATPase, and sodiumpotassium ATPase (Na + /K + -ATPase) govern the uptake and release of calcium ions across cell membrane [49].…”
Section: Effects On Myocardial Calcium Regulation and Rhythmmentioning
confidence: 99%
“…Calcium regulatory proteins such as the sodium-calcium exchanger (NCX), Ca 2+ -ATPase, and sodiumpotassium ATPase (Na + /K + -ATPase) govern the uptake and release of calcium ions across cell membrane [49]. A reduction in intracellular Na + triggers NCX activity to bring more Na + inside the cells in exchange for Ca 2+ [49], while Ca 2+ -ATPase regulates the uptake of Ca 2+ into cells and the sarcoplasmic reticulum (known as sarcoplasmic endoplasmic reticulum Ca 2+ -ATPase (SERCA)) [48]. Kaempferol (100 mg/kg) post-treatment for 45 days reversed the reduction in myocardial membrane-bound Na + /K + -ATPase, Ca 2+ -ATPase, and total ATPase activity in diabetic rats (Table 3) [26].…”
Section: Effects On Myocardial Calcium Regulation and Rhythmmentioning
confidence: 99%